Tanya Bray letter to Thomas Kent regarding the Greater Scaup and other winter sightings, March 5, 1981 - Bray, Tanyaet al (1981)
Tanya Bray letter notes the presence of Greater Scaup and speculates that their numbers might be related to the mild weather. Included with the letter is an annotated list of birds sighted for the winter season. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed